Carbon nanotube blackbody grown on the surface of porous ceramic cavities. (December 2021) - Ando, Wataru; Akashi, Takaya; Watanabe, Hiromichi
Abstract: In order to develop a blackbody on which carbon nanotubes (CNTs) are directly grown, we have searched for the optimal conditions for the growth of CNTs on a porous ceramic cavities based on the chemical vapor deposition (CVD) method using ferrocene and acetylene as the catalyst precursor and carbon source for the CNT growth, respectively. The comparisons of the emissivities, carpets thickness, and crystallinity of CNTs grown on two different pore-size silicon carbide substrates and under various CVD conditions have indicated that the CNT grown under the ferrocene sublimation and CNT growth temperatures of 220 °C and 780 °C, respectively, exhibits both the highest crystallinity and visible spectral emissivity. The emissivity of CNTs clearly increase as the CVD gas pressure increases, though the thickness of the CNT carpets slightly decreases as the pressure increases.